The Emplantation of Christianity: An Anthropological Examination of the Korean Church - Grayson, James H. (Transformation, 2009)
The 'Model for the Emplantation of Religions' can be a useful tool for both the historian and the missioner. Focussed on Korea, this study explains how Christianity became rooted there in a relatively short period of time. Overcoming a significant conflict of core values between Confucianism and Christianity, the Protestant and Catholic churches in Korea have experienced greater and more rapid growth than any other national church in East Asia during the twentieth century. The author identifies three phases in this process of emplantation: 'Contact and Explication', 'Penetration', and 'Growth and Contention'. The continued explanation of belief and teaching is essential for the spread and maintenance of Christianity.